Iron ore prices and the value of the Australian dollar - Haque, M.; Topal, Erkan; Lilford, E. (Maney Publishing, 2015)
Continued strong Chinese demand for Australia's iron ore has ensured that this commodity is singularly the highest value-ranking, exported mineral commodity for this country. As a consequence, the iron ore price and the value of the Australian dollar have substantial influences on the Australian economy. In this empirical study, the aim is to investigate the long-term relationship and the strength of association between iron ore prices and the corresponding exchange rate (AUD/USD). Several assessments for unit root tests have been performed to examine whether the time series data are stationary or not, and the assessments have revealed that the results from all of the tests have confirmed both the iron ore prices and the AUD/USD exchange rates data are non-stationary in levels and stationary in first differences, being I(1) stationary. Johansen cointegration tests have been performed for examining the cointegrating relationships, and have exposed the evidence in favour of a long-term relationship between iron ore prices and the AUD/USD exchange rate. Furthermore, the stability of the relationship has been presented and, thereafter, examined the Granger causality through a vector error correction model (VECM) and a vector auto regression (VAR) test, respectively. From the Granger causality test, it is apparent that there is a one-directional causality between iron ore prices and the AUD/USD exchange rate, implying that iron ore prices generate Granger causes to the AUD/USD exchange rates whereas, conversely, the exchange rate does not have significant Granger causes on iron ore prices. However, while the structural vector auto regression (SVAR) is considered, interestingly, the impulse-response functions (IRFs) analysis revealed that owing to the shocks on AUD/USD exchange rates, iron ore prices have significant responses too, and vice versa.